Unraveling human transferrin-tryptamine interactions: a computational and biophysical approach to Alzheimer’s disease therapeutics - Alrouji, Mohammed; Alshammari, Mohammed S.; Majrashi, Taghreed A.; Zuberi, Azna; Shahwan, Moyad; Atiya, Akhtar; Shamsi, Anas (Frontiers in Pharmacology, 2025)
Neurodegeneration is a progressive loss of neurons that leads to affected cognitive and motor functions and is characterized by neurodegenerative disorders (NDs). Human transferrin (Htf) is a blood plasma glycoprotein that binds to iron and regulates the free iron in biological fluids. Free iron is a potent neurotoxin associated with the generation of Reactive oxygen species (ROS) and is ultimately linked to oxidative stress and neuronal damage. Thus, targeting iron homeostasis is an attractive strategy for the management of NDs, viz. Alzheimer's disease (AD). Tryptamine (Trp) is a naturally occurring monoamine, that has demonstrated promising roles in AD therapeutics. The present study aims to delineate the binding mechanism of Trp with Htf employing computational and spectroscopic approaches. Molecular docking ascertained the vital residues governing the Htf-Trp complex formation. Further, Molecular dynamic (MD) studies ascertained the structural dynamics and stability of the complex, implying that the binding of Trp causes minimal structural alterations in Htf, suggestive of the stability of the complex. The results from fluorescence spectroscopy demonstrated the binding of Trp with Htf with a binding constant (K) of 0.48 × 106 M−1, validating the in silico observations. This study provides a platform to understand the binding mechanism that may lead to novel therapeutic approaches targeting AD.